Relative unpalatability of leaf beetles with either biosynthesized or sequestered chemical defence - Rahier, Martine; Pasteels, Jacques M.; Alonso-Media, A.; Brower, L. P. (My University, 1995)
Defence of leaf beetles in the genus Oreina is chemically diverse. Some (e.g. O. gloriosa) rely on the secretion of small quantities of a concentrated mixture of cardenolides that are biosynthesized de novo and stored only in special glands. Others (e.g. O. cacaliae) lack cardenolides but sequester pyrrolizidine alkaloid N-oxides (PAs) and store them both in their body and in their glands. First, the impact of the defensive secretions on the palatability of the beetles to wild-caught red-winged blackbirds, Agelaius phoeniceus, was tested. The reactions of the birds to these two different types of chemicals were then compared to determine whether they grant equal protection to the beetles. Oreina gloriosa, with their secretion of cardenolides intact, were eaten in 55% of the trials. When the secretion was physically removed, 95% of the now undefended O. gloriosa were eaten. The mean handling time by the birds also decreased from 41 to 26 s. This shows that the small quantity of highly concentrated secretion produced on the surface of the beetle's body affords substantial protection against avian predators. Oreina cacaliae, with PAs in their secretion and in their body, were eaten in only 21% of the cases. When the secretion was removed, leaving PA only in the body, the number eaten rose to 36%. The time to peck and then reject the beetles with their secretions intact was less in O. cacaliae than in O. gloriosa. PAs therefore seem to provide the beetle with better protection from the birds than do cardenolides. The experiment raised the possibility that the birds may have the ability to reject beetles with PAs olfactorily.